Effects of acidic beverages on color stability of Bulk-fill composites with different viscosities = Efectos de las bebidas ácidas sobre la estabilidad del color de resinas tipo Bulk con diferentes viscosidades - Şişmanoğlu, Soner
The aim of this in vitro study is to investigate the effects of acidic beverages on the discoloration of bulk-fill composites with different viscosities. 144 disc-shaped specimens (8mm diameter × 2mm thick) were prepared from four different composite resins including a nanohybrid (Filtek Ultimate), two packable bulk-fill (Filtek Bulk Fill, Tetric N Ceram Bulk Fill), and a flowable bulk-fill composite (Tetric N Flow Bulk Fill). The specimens of each group were divided into 3 subgroups and submerged in distilled water, orange juice and coke (n=12). Color difference (ΔE) were measured using CIELab color space and a compact spectrophotometer (VITA Easyshade) at baseline and after 30 days of immersion. Data were analyzed using two-way ANOVA and Tukey's HSD post-hoc tests (P<0.05). Two-way ANOVA revealed that both material type and staining solution significantly influenced ΔE values (P<0.001). Immersion in orange juice resulted in greater and significant discoloration over time in comparison to distilled water and coke (P<0.05). Tetric N Ceram (ΔE=7.0) and Tetric N Flow (ΔE=7.7) bulk-fill restoratives showed highest color change values after 30 days of immersion in orange juice. This study suggests that a discoloration above the clinically acceptable threshold (ΔE>2.7) was observed for all bulk-fill composites tested. It can be speculated that orange juice has a more negative effect on the color stability compared to coke. Additionally, flowable bulk-fill composite was more prone to discoloration than condensable bulk-fill composites.